International Migrants in Johannesburgs Informal Economy - Peberdy, Sally (Migration policy series ;, 2016)
This report provides a rich view of the activities of migrant entrepreneurs in the informal economy of Johannesburg. It is hoped that the information will facilitate understanding of the informal sector and its potential, and not just in the context of migrant entrepreneurs. The informal economy plays a significant role in the entrepreneurial landscape of the City of Johannesburg and is patronized by most of the city's residents. The research presented here challenges commonly held opinions about migrant entrepreneurs in the City of Johannesburg and shows that they do not dominate the informal economy, which remains largely in the hands of South Africans. In late 2013, the City, through Operation Clean Sweep, removed up to 8,000 traders from the city's streets. As this and recent xenophobic attacks demonstrate, Johannesburg can be a hostile place in which to operate a business as an informal economy migrant entrepreneur. Instead of trying to sweep the streets clean of these small businesses, government at national, provincial and city levels should develop policies to grow the SMME economy, develop township economies, and manage the informal economy and street trading. They need to incorporate the businesses owned by migrant entrepreneurs, rather than exclude and demonize them. These businesses make an invaluable contribution to Johannesburg's economy despite operating in a non-enabling political and policy environment.